(untitled) (Journal of Nobel Medical College, 2015)
A prospective study of forty comminuted femoral shaft fractures, open and close, treated with a relatively minimally invasive technique termed as bridge plate osteosynthesis or biological fixation. Less invasive procedure, Short operative time and less blood loss was seen during surgical procedure. This prospective study was conducted at Nobel Medical College, Biratnagar from 2010 to 2011. This study was done because most of the femoral shaft fractures treated under C-arm mobile image intensifier but bridge plating system does not require such advanced costly equipment. Almost all cases were free from long term complications. All fractures healed within 6 months. Bone grafting was done for 2 cases as a secondary procedure. The complication of infections was seen in two of open fractures. This procedure can easily be carried out in general operating table by appropriable surgeons. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.12230 Journal of Nobel Medical College Vol. 3, No.1 Issue 6, 2014, Page: 7-12